2018
DOI: 10.1097/md.0000000000013465
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban versus enoxaparin for the prevention of venous thromboembolism after total knee arthroplasty

Abstract: Objective:This article analyzed the clinical efficacy and tolerability of rivaroxaban and enoxaparin in patients undergoing total knee arthroplasty (TKA) surgery.Methods:Five randomized, controlled clinical trials on rivaroxaban versus enoxaparin in patients who underwent TKA were identified and included in this meta-analysis.Results:The meta-analysis indicated that rivaroxaban prophylaxis was associated with lower rates of symptomatic venous thromboembolism (VTE) (relative risk[RR]:0.55; 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
(38 reference statements)
2
15
2
1
Order By: Relevance
“…Rivaroxaban, which is included in the novel anticoagulant (NOAC) group, works through the direct inhibition of factor Xa, which is involved in coagulation [ 22 ]. Factor Xa is involved in the common pathway, and its inhibition leads to the prevention of clot formation and thrombin generation [ 22 , 23 ]. It reversibly and competitively binds to circulating and clot-bound factor Xa through S1 and S4 pockets, resulting in high selectivity to factor Xa compared to other factors [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivaroxaban, which is included in the novel anticoagulant (NOAC) group, works through the direct inhibition of factor Xa, which is involved in coagulation [ 22 ]. Factor Xa is involved in the common pathway, and its inhibition leads to the prevention of clot formation and thrombin generation [ 22 , 23 ]. It reversibly and competitively binds to circulating and clot-bound factor Xa through S1 and S4 pockets, resulting in high selectivity to factor Xa compared to other factors [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factor Xa is involved in the common pathway, and its inhibition leads to the prevention of clot formation and thrombin generation [ 22 , 23 ]. It reversibly and competitively binds to circulating and clot-bound factor Xa through S1 and S4 pockets, resulting in high selectivity to factor Xa compared to other factors [ 22 , 23 ]. The direct and selective action of rivaroxaban is shown to increase effectivity compared to other indirect factor Xa inhibitors such as VKA or LMWH [ 5 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have proven effective in preventing venous thromboembolism after orthopaedic surgery, for stroke prevention in patients with atrial fibrillation, and have been approved for the treatment of deep vein thrombosis and pulmonary embolism. [9][10][11][12][13][14][15][16][17] There are also studies comparing the use of direct oral anticoagulants with LMWH for the prevention of venous thromboembolism in orthopaedic surgery where it is more effective in the prevention of venous thromboembolism after arthroscopy compared with enoxaparin, without increasing the risk of major bleeding. [11][12][13] Data from meta-analyses and randomised trials of patients with venous thromboembolism report similar efficacy and reduced rates of bleeding when direct oral anticoagulants are compared with vitamin K antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] There are also studies comparing the use of direct oral anticoagulants with LMWH for the prevention of venous thromboembolism in orthopaedic surgery where it is more effective in the prevention of venous thromboembolism after arthroscopy compared with enoxaparin, without increasing the risk of major bleeding. [11][12][13] Data from meta-analyses and randomised trials of patients with venous thromboembolism report similar efficacy and reduced rates of bleeding when direct oral anticoagulants are compared with vitamin K antagonist. [18][19][20][21][22][23][24][25] A recent meta-analysis suggested that single thromboprophylaxis with rivaroxaban is more effective in the prevention of deep vein thrombosis in elective total knee replacement than combination strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation